Evaluation of the Impact of Iron Deficiency Anemia during Pregnancy on Hospital Admission and Utilization of Hospital Resources in Latifa Women and Children Hospital, Dubai, UAE - Nighat Aftab; Saima Faraz; Komal Hazari; Asma Fahad; Nadia AlSawalhee; Amal AlQedrah; Shazia Naqvi; Litty Paulose; Widad Abdelkareem; Taghrid EL Gergawi (Dubai Medical Journal, 2021)
Introduction: Iron deficiency anemia (IDA) is endemic among pregnant females worldwide. Liposomal iron preparation is a novel therapy for treating IDA in pregnant females. There is a lack of research on cost-effect and comparison between various new iron preparations as liposomal and intravenous (IV) iron supplements in the international literature. Objective: The objective of this study was to evaluate the cost-effect and maternal-fetal outcome of IDA during pregnancy in Latifa Women and Children Hospital, Dubai, UAE. Design: The study was a quasi-experimental study. Settings: Settings include tertiary-care hospital settings affiliated with academic center in UAE. Patients and Methods: A total of 226 pregnant women were inducted in the study who were controlled in terms of age, BMI, baseline hemoglobin (Hb), severity of anemia, and ferritin levels. There were 116 patients who received oral liposomal iron pyrophosphate and 110 patients received IV iron saccharate complex for 4 weeks. The overall cost-effect and maternal-fetal outcomes were compared in 2 groups. Main Outcomes Measured: The main outcomes measured the cost-effect of liposomal and IV iron therapy, and the 2 treatments were compared in terms of maternal and fetal outcomes. Result: The subjects were matched for age and body mass index and showed that the patients in the IV group were more symptomatic than those in the oral group (18.1 vs. 31.9% p value <0.01). There was no statistically significant difference among women from different nationalities living in UAE (p value 0.079). There were 98 (84.4%) patients in the oral group and 99 (90%) patients in the IV group who achieved the desired Hb levels after 1 month of treatment (p value = 0.878). Moreover, the side effects were also comparable in both groups (1.72 vs. 1.82% p value = 0.56). The incremental cost-effect ratio for IV iron was USD 108,633/rise to desired Hb. Conclusion: Liposomal iron preparations may be cost-effective and have fewer side effects than IV iron. In terms of outcome, the maternal and fetal variables are comparable in liposomal and IV groups.